2014
DOI: 10.1021/jp5092784
|View full text |Cite
|
Sign up to set email alerts
|

Solvation and Rotation Dynamics in the Trihexyl(tetradecyl)phosphonium Chloride Ionic Liquid/Methanol Cosolvent System

Abstract: The interactions and solvent structure in trihexyl(tetradecyl)phosphonium chloride ionic liquid ([P(14,6,6,6)(+)][Cl(-)], "PIL-Cl")/methanol (MeOH) solutions across the entire range of mole fraction PIL-Cl (x(IL) = 0-1) are discussed. Viscosity and conductivity measurements are used to characterize the bulk solvent properties. At x(IL) < 0.1, the log(η) data show a nonlinear dependence on mole fraction in contrast to the data for x(IL) > 0.1 where the data vary linearly with mole fraction. Conductivity data sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 100 publications
4
26
0
Order By: Relevance
“…Ionic liquids are often reported to contain a small fluorescence background, and our previous work with [P 6,6,6,14 ] + Cl − is consistent with that observation [22,59,66], showing a broad, featureless emission spectrum with ν pk em = 479 nm [59]. Excitation and emission scans of neat CO 2 showed that it was free from any fluorescent impurities, however, there was measurable pressure-dependent emission when [P 6,6,6,14 ] + Cl − was added to CO 2 .…”
Section: Steady-state Spectroscopysupporting
confidence: 82%
See 2 more Smart Citations
“…Ionic liquids are often reported to contain a small fluorescence background, and our previous work with [P 6,6,6,14 ] + Cl − is consistent with that observation [22,59,66], showing a broad, featureless emission spectrum with ν pk em = 479 nm [59]. Excitation and emission scans of neat CO 2 showed that it was free from any fluorescent impurities, however, there was measurable pressure-dependent emission when [P 6,6,6,14 ] + Cl − was added to CO 2 .…”
Section: Steady-state Spectroscopysupporting
confidence: 82%
“…The instrument was calibrated using the water Raman signal and all spectra were blank subtracted and corrected for instrument response. Time-resolved emission intensity decays were measured using the Fluorolog-3 instrument, modified with time-correlated single photon counting (TCSPC) components from Horiba Scientific as described elsewhere [59]. In this work, all time-resolved measurements were excited with a 405 nm NanoLED (405-L) high output diode laser operating at a 1 MHz repetition rate, controlled through a FluoroHub controller that was run by DataStation (2.6) software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For time-dependent emission, our instrument was modified to include time-correlated single photon counting (TCSPC) components, which has been previously discussed [57,72]. For these experiments, all time-resolved decay measurements were excited using a 405 nm diode laser, high output NanoLED, from Horiba.…”
Section: Methodsmentioning
confidence: 99%
“…A non-linear dependence of viscosity on mole fraction was observed below X IL o0.1 while the data vary linearly with mole fraction for X IL 40.1. 156 Studies on mutual miscibility of tetrafluoroborate PILs with common solvents, such as cyclic hydrocarbons 157 and diols 158 were also reported. Mixtures of immiscible ionic liquids including PILs were investigated by Palomar and co-workers, 159 demonstrating the potential of biphasic IL mixtures for extraction/ separation procedures.…”
Section: Preparation and Characterisationmentioning
confidence: 99%